2020
DOI: 10.1128/mbio.00353-20
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Enteroaggregative Escherichia coli within the ST131 Lineage as a Cause of Extraintestinal Infections

Abstract: Escherichia coli sequence type 131 (ST131) is a major cause of urinary and bloodstream infections. Its association with extended-spectrum β-lactamases (ESBLs) significantly complicates treatment. Its best-described component is the rapidly expanding H30Rx clade, containing allele 30 of the type 1 fimbrial adhesin gene fimH. This lineage appears to have emerged in the United States and spread around the world in part due to the acquisition of the ESBL-encoding blaCTX-M-15 gene and resistance to fluoroquinolones… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
(61 reference statements)
0
26
0
1
Order By: Relevance
“…In line with this, younger women with a low or moderate- Lactobacillus dominated urotype have been found to be associated with mixed urinary incontinence, pointing towards a dysbiosis in women lacking Lactobacillus 32 . Conversely, it might represent personal variations in the urinary microbiota or be influenced by temporal factors that could change the microbial composition, such as menstruation or coitus 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, younger women with a low or moderate- Lactobacillus dominated urotype have been found to be associated with mixed urinary incontinence, pointing towards a dysbiosis in women lacking Lactobacillus 32 . Conversely, it might represent personal variations in the urinary microbiota or be influenced by temporal factors that could change the microbial composition, such as menstruation or coitus 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, use of 16S rRNA gene sequencing and enhanced bacteria culture may give different urinary microbiota results 9 and one may argue that both methods should be included to proper reflect the microbiota of the bladder. Fourth, we only collected urine at a single timepoint, and as the bacterial composition has been shown by some to fluctuate over time 33 , this possible lack of temporal stability may have impacted the results. We have, however, previously shown that the composition of the urinary microbiota remains stable over a shorter time period 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the definition of ST69 as a high-risk clone, with increased ability for antimicrobial resistance genes acquisition. Moreover, the presence of type 1 fimbriae (fimH27), has been correlated with persisting colonization and bacteremia in patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…The broadly reported multidrug resistant E. coli ST131 is example of highly virulent ExPEC associated with urinary and bloodstream infections. It has also acquired enteroaggregative diarrheagenic phenotype due to pAA plasmid presence ( Boll et al., 2018 ). Many others HyPEC are described as case report, but not fully characterized.…”
Section: Genetic Plasticity and Emergent E Coli Pmentioning
confidence: 99%